1992
DOI: 10.1121/1.404482
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stud type and spacing, screw spacing, and sound absorbing material on the sound transmission through a double panel wall specimen

Abstract: sponse in order to obtain accurate phase information. SYSid then uses FFT techniques to deconvolve the stimulus from the measured response and to further analyze the data. From this basic mode of operation SYSid can perform many types of analyses including phase responses, group delay, impulse response, Hilbert envelope, reverse energy time curve, RT60, waterfall displays, electrical impedance, etc. In addition to these linear measurements, SYSid also provides the capabilities to make distortion measurements d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…11,12 Low-frequency dips in transmission loss versus frequency curves shifted to lower frequencies when the stud spacing or the spacing of the screws holding the gypsum board into wood studs was increased. The effect of varied stud spacing is qualitatively similar to that reported in this article.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Low-frequency dips in transmission loss versus frequency curves shifted to lower frequencies when the stud spacing or the spacing of the screws holding the gypsum board into wood studs was increased. The effect of varied stud spacing is qualitatively similar to that reported in this article.…”
Section: Discussionmentioning
confidence: 99%
“…These calculations would also explain why the assumption of normal incidence appears to work reasonably well. Quirt and Warnock (1993) have shown that the sound insulation of wooden stud walls is strongly dependent on the screw spacing while the sound insulation of steel stud walls only varies slightly with screw spacing. Thus it may be that the line connection theory is adequate for steel stud walls; if suitable a stud compliance as a function of frequency can be determined (Davy et al, 2012).…”
Section: Resilient Massless Point Connectionsmentioning
confidence: 98%
“…8 and 9. In general, when a fibrous absorber is installed in the cavity, sound insulation increases with increasing internal sound reduction of the absorber, that is, with increasing density or thickness of the absorber [1][2][3][4]. However, from these results, it can be deduced that the sound insulation depends on the acoustic resistance but not on the sound absorption coefficient, because the absorption coefficient becomes unity at resonance frequency f 0 when the acoustic resistance is unity.…”
Section: Relationship Between Acoustic Impedance Ofmentioning
confidence: 99%
“…However, this is not the best strategy because it increases the wall's total weight and thickness. Installing fibrous absorbers in the cavity improves sound insulation only at mid-and high frequencies; these absorbers have less effect on sound insulation at low frequencies including f rmd [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%